2005
DOI: 10.1111/j.1572-0241.2004.40665.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Terlipressin and High Somatostatin Dose during Acute Variceal Bleeding in Nonresponders to the Usual Somatostatin Dose

Abstract: In nonresponders to usual somatostatin dose, both terlipressin and high-dose of somatostatin infusion significantly decreased HVPG and increased the rate of hemodynamic responders. Such effects were greater with terlipressin. Both treatments may be an alternative when standard somatostatin fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…That is why it is recommended to start treatment by administering an intravenous bolus (250 mcg), repeated if necessary, followed by the continuous intravenous infusion of 250 mcg/h. A recent study showed that, in patients showing a very scarce response (<10 % fall in portal pressure) to 250 mcg/h of somatostatin, both the infusion of 500 mcg/h of somatostatin or the administration of 1 mg of terlipressin resulted in almost twice the decrease in portal pressure [43]. Moreover, a clinical study demonstrated that in patients actively bleeding at initial endoscopy, the infusion of 500 mcg/h of somatostatin achieved a greater control of hemorrhage, a reduced incidence of early rebleeding, and reduced the mortality at 1 and 6 weeks and the transfusional requirements, as compared with the standard dose of 250 mcg/h [44].…”
Section: Somatostatin and Somatostatin Analoguesmentioning
confidence: 97%
“…That is why it is recommended to start treatment by administering an intravenous bolus (250 mcg), repeated if necessary, followed by the continuous intravenous infusion of 250 mcg/h. A recent study showed that, in patients showing a very scarce response (<10 % fall in portal pressure) to 250 mcg/h of somatostatin, both the infusion of 500 mcg/h of somatostatin or the administration of 1 mg of terlipressin resulted in almost twice the decrease in portal pressure [43]. Moreover, a clinical study demonstrated that in patients actively bleeding at initial endoscopy, the infusion of 500 mcg/h of somatostatin achieved a greater control of hemorrhage, a reduced incidence of early rebleeding, and reduced the mortality at 1 and 6 weeks and the transfusional requirements, as compared with the standard dose of 250 mcg/h [44].…”
Section: Somatostatin and Somatostatin Analoguesmentioning
confidence: 97%
“…This response may improve by doubling the dose of somatostatin or switching to another agent (such as terlipressin). 50 …”
Section: Hvpg Measurements In Acute Variceal Hemorrhagementioning
confidence: 99%
“…However, scant evidence exists that this reduction will affect the risk of a primary bleeding episode in PHG patients [72,103,104,269,270] . Propranolol is recommended regardless of the severity or presence of PHG in patients with esophageal varices because it treats both entities by reducing portal pressure [105][106][107]198,271,272] . Prophylaxis of bleeding from PHG is not recommended [260] .…”
Section: Preventionmentioning
confidence: 99%